A humean account of testimonial justification - RYAN, Shane (Institutional Knowledge at Singapore Management University, 2014)
I argue that a Humean account can make sense of the phenomenology associated with testimonial justification; the phenomenology being that in standard cases hearers regularly simply accept a testifier’s assertions as true – hearers don't engage in monitoring. The upshot is that a Humean account is in a better position dialectically than is usually supposed. I provide some background to the debate before setting out two challenges facing accounts of testimonial justification. The first challenge is to provide an account that accords with the phenomenology of testimonial reception; the second challenge is to provide an account that can make sense of some testimonial beliefs enjoying greater justification than others. I show the credulist position to be vulnerable to the second challenge and the Humean position to be vulnerable to the first challenge. I argue that a Humean account, by drawing on dual process theory, can overcome the first challenge.